Psychometric validation of the Malay version of the Ryff Psychological Well-Being Scale for caregivers of patients with dementia - Mohammed Rasheedan, Ellin; Vimala, Ramoo; Nor Aziyan, Yahaya; Tan, Maw Pin; Dayang Zuraina, Abang Haji Kashim (UNIMAS Publisher, 2026)
Despite its widespread international use, the Ryff Psychological Well-Being Scale lacks a culturally validated Malay version, highlighting the need for a reliable tool to assess psychological well-being in Malaysia. Psychological well-being is a multifaceted construct that requires culturally appropriate instruments. The Malay version was developed using rigorous forward-backwards translation to ensure linguistic accuracy and cultural relevance, followed by review from eight experts in psychology, medicine, and gerontology who assessed item clarity, relevance, and cultural suitability. Minor modifications were applied to improve readability without altering underlying constructs. Content validity evaluation showed high item-level and scale-level Content Validity Index (CVI) values, indicating strong agreement among experts. Reliability testing yielded a Cronbach's alpha of 0.865, confirming the robustness of the translated scale, though further evaluation may enhance its psychometric properties. These findings provide a reliable, culturally validated instrument for assessing psychological well-being among Malay-speaking populations, supporting both research applications and evidence-based practice, and facilitating cross-cultural mental health studies.